Effect of Shot Peening on Fatigue Strength of High‐Toughness Spring Steel. Issue 12 (20th September 2013) - Harada, Yasunori; Kosaka, Hiroki; Ishihara, Makoto
Abstract : The shot peening process is a widely used surface treatment method for improving fatigue strength and anti‐wear characteristics. The surface of the material receives a so‐called peening effect where strong local deformation forms a work‐hardened layer or causes compressive residual stress. In the present study, the effect of shot peening on fatigue strength of high‐toughness spring steel was investigated. The optimum conditions were evaluated in an experiment using the conventional shot peening machine with shots of an average size. The projective method of the shot media was of the centrifugal peening type. The shot media of 1.0 mm diameter was high‐carbon cast steel, and the workpiece used was the commercially spring steel JIS‐SUP10. The effects of peening time have primarily on surface characteristics and fatigue strength were studied. Fatigue tests were carried out in a plane‐bending test machine. S – N curves were established for unpeened and peened conditions. The main results were as follows: the surface layer of the workpieces was sufficiently deformed by shot peening. The residual stress was added in the surface vicinity on all peened workpieces. As the peening time increased, the region with residual stress extends in the depth direction. The value of maximum compressive residual stress was about 950 MPa. At a large number of cycles to fracture, shot peening could more effectively enhance the fatigue strength. When shot velocity was 60 m s −1, the maximum fatigue strength was about 525 MPa with a peening time of 90 s. This peening time was nearly equal to the full coverage time. It was found from the present experiment that the optimum peening time for the conventional shot peening was about 90 s. Abstract : Shot peening using conventional cast steel shots is conducted for the purpose of improving the fatigue characteristics of spring steel. To examine the effect of shot peening on fatigue strength, fatigue tests are carried out in a plane‐bending test machine. It is found that the full‐coverage time, 90 s, is required in order to improve the fatigue life.